PENGARUH NPM DAN ROA TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PADA PERIDOE 2016-2020 - Nathania Jennifer; Remista Simbolon (Jurnal Ekonomis, 2021)
Profit growth rate is important for every company. This study was conducted to determine the effect of NPM and ROA on Profit Growth in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange. The population used in the research is food and beverage companies listed on IDX in 2016-2020. Sampling in this study was carried out using purposive sampling so that there were 14 companies with five years of observation so that 70 sample data were obtained, but because there were 7 outliers, the sample used was 63 data. The results of this study state that NPM on profit growth seen from the correlation coefficient has a very weak r-count, in the significance test it does not have a significant relationship, in the coefficient of determination it has a weak contribution (0.004) and has a positive effect. ROA on profit growth seen from the correlation coefficient has a weak relationship, in the significance test it has a significant relationship (1.839 > 1.671), in the contribution determination coefficient it is still very weak, in a simple regression it has a positive effect. Simultaneously NPM and ROA seen from ANOVA simultaneously have a significant effect on profit growth (0.025 <0.05).